Petrarquismo en octosílabos: del Cancionero de Urrea al de Pedro de Rojas. - Alonso, Álvaro (Cuadernos de Filología Italiana, 2005)
This article deals with Italian influence over Spanish octosyllables. It brings into focus three kinds of images: those related to mythology, to descriptio puellae and to witty Petrarchism. Taking the analysis of these images as its starting point, the present paper proposes that spanish octosyllables were renewed from 1560 onwards, and that they were influenced by poesia cortigiana rather than by bembian Petrarchism.